(3GdadGMIs - (3GHf GdYhGe GdGTHjdj , jMji Hf eMeO Hf CMeO Hf GdYhGe GdGTHjdj, CHh RcQjG,J (B580 (3g` s
(3ChdgG (B:s
(3GeG HYO (B: (3aEfi deG bQGJ ef cJH GdadGMI ddeSdejf GdCfOdSjjf , hef cJH ZjQge ef GdbOeGA GdebOejf s
(3BNQgG (B:s
(3hGfG GSJZaQ Gddg ef GdNWC hGdRdd , hGSCdg GdeZaQI hGdQMeI hGdJhajb dUGdM GdYed hGdbhd dG QH ZjQg hdGeYHhO ShGg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B252 - (3U(B325s
(3LRAGf ai eLdOs
(3eUhQI Yf eNWhW HGQjSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B165 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B222s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B494 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B903 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa (B- (3U (B187 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdRQGYI h GdCYTGHs